2019
DOI: 10.1186/s12903-019-0823-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two educational interventions on primary school teachers’ knowledge and self-reported practice regarding emergency management of traumatic dental injuries

Abstract: Background The present study evaluated the effect of two educational interventions on the knowledge and self-reported practice of primary school teachers regarding emergency management of traumatic dental injuries (TDIs). Methods All primary school teachers ( n = 664) of Arak, Iran were asked to participate in the study. Based on geographic regions, all participants were enrolled in two groups: educational leaflet and oral presentation. At bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 27 publications
2
32
0
2
Order By: Relevance
“…Finally, 32 studies were included for data extraction ( Figure 1 ). Table 1 presents a summary of the studies that addressed TDI education and Table S1 presents full summary of studies focused on education in TDI [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 32 studies were included for data extraction ( Figure 1 ). Table 1 presents a summary of the studies that addressed TDI education and Table S1 presents full summary of studies focused on education in TDI [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The geographical distribution of the records revealed that 40.6% ( n = 13) were from the Middle East region (Israel [ 21 , 26 ], Kuwait [ 22 , 23 , 44 ], Iran [ 33 , 37 , 38 , 50 ], Turkey [ 28 ], Lebanon [ 32 , 45 ], United Arab Emirates [ 46 ]), 18.7% ( n = 6) from India [ 27 , 34 , 39 , 43 , 48 , 49 ], 12.5% ( n = 4) from Brazil [ 25 , 40 , 42 , 47 ], 6.3% ( n = 2) from Hong Kong [ 35 , 36 ], USA [ 21 , 41 ], and Poland [ 30 , 31 ], and 3.1% ( n = 1) from Tanzania [ 19 ], Switzerland [ 24 ], and Australia [ 29 ]. Most papers included in this scoping review ( n = 23, 71.9%) were published between 2012 and 2018 [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These areas include the management of avulsed and fractured teeth in terms of handling the tooth, storing it in the proper transportation medium and when to seek professional care. The identification of these areas may help educators, clinicians, administrators and policymakers to formulate an effective oral health education and promotion programme for the public, similar to the efforts already conducted for schoolteachers, parents and nurses in other countries 20–23 . Perhaps empowering non‐healthcare professionals such as schoolteachers and physical educators to create an awareness of TDI management would be a worthwhile approach, given their access to children and caregivers 24,25 .…”
Section: Discussionmentioning
confidence: 99%